Effects of 5 weeks high-intensity interval training vs. volume training in 14-year-old soccer players - Sperlich, B.; de Marees, M.; Koehler, K.; Linville, J.; Holmberg, H. C.; Mester, J. (The Journal of Strength and Conditioning Research, 2011)
High-intensity interval training (HIIT) in junior and adult soccer has been shown to improve oxygen uptake (Vo2) and enhance soccer performance. The main purpose of this study was to examine the short term effects of a 5-week HIIT vs. high-volume training (HVT) program in 14-year-old soccer players regarding the effects on Vo2max and 1,000-m time (T1000) and on sprinting and jumping performance. In a 5-week period, 19 male soccer players with a mean (SD) age of 13.5 ± 0.4 years performed HIIT at close to ~90% of maximal heart rate. The HVT intensity was set at 60-75% of maximal heart rate. Vo2max increased significantly (7.0%) from pre to post in HIIT but not after HVT. T1000 decreased significantly after HIIT (~-10 vs. ~-5 seconds in HVT). Sprint performance increased significantly in both groups from pre to posttesting without any changes in jumping performance.